Stratégies De Gestion Des Conflits Fonciers Intra Familiauxà Douafla Dans La Sous-Préfecture De Sinfra (Centre-Ouest Ivoirien) - Fallé Landry Yves (European Scientific Journal, ESJ, 2018)
Our study is focused on intra-family conflicts in the locality of Douafala at the sub-prefecture of Sinfra in the west center of Cote d'Ivoire. It has helped us to understand and analyze the causes of intra-family conflicts within the families of Douafla and the processes used in solving them. The argument is that intra-family land conflicts take many forms in the locality of Douafala and the actors use specific techniques to resolve these conflicts. The study was guided by the main question: What are the intra-family land conflicts existing in Douafla which justifies the land conflicts existing within the family unit? To answer this question, we have developed three hypotheses from the three specific objectives. Indeed, the first objective was to identify intra-family conflicts in Douafla. The second objective was to analyze the intra-family conflicts and the adopted (customary and administrative) strategies of this conflict. Finally, the last objective was to analyze the procedures adopted by the authorities in the resolution of this conflict. At the end of our analysis, we stated that land in all its forms generates conflicts that are sometimes adjustable. Land conflicts, therefore, arise due to generosity in the past and the lack of paper document of the land.